Enhancing Safety and Slip Resistance of Epoxy Flooring Materials through the Reuse of Aluminum Machining Chips - Sami, Abdelhalim; ali, Salih Eltahir Elmarud; ali, Abdulrahman Khamaj; ali, Abdullah A. Faqihi; Bafakeeh. O. T (Journal of King Abdulaziz University: Engineering Sciences, 2024)
The present study is part of a wide research project conducted by the authors. The overarching purpose of this project is to explore the reuse of aluminum machining chips for the development of design recommendations for epoxy floor materials, specifically focusing on safety requirements and slip resistance based on friction measurements. The aim is to address the potential danger of electrostatic charge generation during walking. Epoxy floor coatings are commonly used in commercial and industrial settings. They are typically applied over concrete floors to create a smooth, durable surface that can withstand heavy loads and provide a high-performance flooring solution. Many industrial sites, warehouses, and commercial buildings rely on epoxy floors to maintain clean and safe conditions for workers, equipment, and inventory.